The ROLE OF LIFESTYLE IN MEDIATING THE INFLUENCE OF DIGITAL TRANSACTION SERVICE INNOVATION ON GO-PAY SERVICE USER DECISIONS - Siregar, Ade Perdana; Setiawan, Wahyu Juari (Journal of Business Studies and Management Review, 2024)
The development of very advanced technology, leads to changes in the lifestyle of every human being, including the marketing and financial fields have developed towards a more efficient and modern direction. The purpose of this study is to identify the influence of digital transaction service innovation on service user decisions, identify the influence of digital transaction service innovation on lifestyle, identify the influence of lifestyle on service user decisions and identify the role of lifestyle in mediating the influence of digital transaction service innovation on Go-Pay service user decisions. The independent variable used is innovation with indicators of relative advantage, compatibility, complexity, divisibility and communicability. The mediating variable is lifestyle with indicators of activities, interest and opinion while the dependent variable is the decision of the service user. This study was conducted on Go-Pay service users in Jambi City and data obtained through the distribution of questionnaires. The data analysis method used is Structural Equation Modeling (SEM) measurement using SmartPLS software. To see the role of lifestyle in mediating the influence of digital transaction service innovation on Go-Pay service user decisions